2011
DOI: 10.1188/11.onf.e305-e313
|View full text |Cite
|
Sign up to set email alerts
|

Pain Severity, Satisfaction With Pain Management, and Patient-Related Barriers to Pain Management in Patients With Cancer in Israel

Abstract: Nurses should assess for patients' expectations and barriers that could impede pain relief and provide appropriate interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
13
0
2
Order By: Relevance
“…However, prior studies found that both patients and their FCs are most concerned about addiction. 9,12,13,35 Myths and fears about opioid use remain widespread across cultures and across care settings. 4 Antidrug campaigns that attempt to combat trafficking and demand for illicit drugs as well as abuse of prescription opioids may contribute to the perception that analgesics are dangerous even when they are used for the management of cancer pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies found that both patients and their FCs are most concerned about addiction. 9,12,13,35 Myths and fears about opioid use remain widespread across cultures and across care settings. 4 Antidrug campaigns that attempt to combat trafficking and demand for illicit drugs as well as abuse of prescription opioids may contribute to the perception that analgesics are dangerous even when they are used for the management of cancer pain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the provided interventions from clinicians and consistent with a previous report, 15 ratings of pain relief, as well as use of analgesics ( Table 4), suggest that improvements in pain management are warranted. Suboptimal pain relief may be associated with barriers to pain management (eg, fears of tolerance and addiction 34,52 ). Reasons for the persistence of pain and its interference with function were not assessed.…”
Section: Pain Characteristicsmentioning
confidence: 99%
“…[20] Further, several studies have shown that patients can be satisfied with their pain management, despite experiencing severe pain. [22,23] In the original version, feelings of helplessness were loaded on the pain severity and activity subscale instead of the affective subscale. Our study indicated that "Pain causing helplessness" was related to the affective subscale.…”
Section: Discussionmentioning
confidence: 99%